Daring Masif dan Terbuka (Didamba) Merupakan Salah Satu Pembelajaran Berkelanjutan untuk Meningkatkan Profesionalisme Guru - Hartono, Hartono (Jurnal Likhitaprajna, 2020)
The condition of the country that is being hit by the COVID-19, requires the Government to set several policies, one of which is learning at home so that all activities related to the Learning Process are carried out from home. Likewise, activities related to enhancing teacher competence and professionalism are also followed from home, such as Massive and Open Online Education and Training. It is organized by the Center for the Development and Empowerment of Teachers and Natural Science Education Personnel of the Ministry of Education and Culture is an online education and training for teachers of science subjects at the elementary school, junior high school, senior high school and vocational school levels. Massive and Open Online Education and Training is an innovation in implementing education and training with an online model for science subject teachers who want to improve their professionalism. This training encourages teachers to continue to improve their competence, professionalism and innovate in accordance with the demands of current advances in science and technology. it provides opportunities for science teachers to advance and exploit the new abilities they are learning.